login
This site is supported by donations to The OEIS Foundation.

 

Logo

Annual Appeal: Please make a donation (tax deductible in USA) to keep the OEIS running. Over 5000 articles have referenced us, often saying "we discovered this result with the help of the OEIS".

Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A080073 Let f(n)! = n^n. Then f(n) = n g(1/log(n)), where g has the asymptotic series g(x) = Sum a(j) x^j/j!. The given sequence is a(j). 0

%I

%S 1,1,0,-3,4,50,-264,-1638,25264,40896,-3357360,13380840,559239264,

%T -7126367664,-98536058880,3137828374800,8293939695360,

%U -1427422903584000,10789876955529216,666226173751955712,-14427332604300810240,-279534553922071445760

%N Let f(n)! = n^n. Then f(n) = n g(1/log(n)), where g has the asymptotic series g(x) = Sum a(j) x^j/j!. The given sequence is a(j).

%F E.g.f. A(x), safisfies A(x)=1+x*(A(x))*(1-log(A(x)),

%F a(n)=((n-1)!*sum(i=0..n-1, (binomial(n,i)*sum(j=0..n, j!*(-1)^(j)*binomial(n,j)*stirling1(n-i-1,j)))/(n-i-1)!)), n>0, a(0)=1. [_Vladimir Kruchinin_, Oct 13 2012]

%e f(n) = n (1 + 1/log(n) - 1/(2 log(n)^3) + ...), so a(0) = 1, a(1) = 1, a(2) = 0 and a(3) = (-1/2)*3! = -3.

%o (Maxima)

%o a(n):=if n=0 then 1 else ((n-1)!*sum((binomial(n,i)*sum(j!*(-1)^(j)*binomial(n,j)*stirling1(n-i-1,j),j,0,n))/(n-i-1)!,i,0,n-1)); [_Vladimir Kruchinin_, Oct 13 2012]

%K easy,sign

%O 0,4

%A Jim Ferry (jferry(AT)alum.mit.edu), Mar 14 2003

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent | More pages
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy .

Last modified December 7 08:21 EST 2016. Contains 278849 sequences.